Electroconvulsive Therapy Use in Major Depressive Disorder Hospitalizations in Portugal - Marta Araújo; Alberto Freitas; Manuel Gonçalves Pinho (Revista Portuguesa de Psiquiatria e Saúde Mental)
Introduction: Depression, recognized as a major contributor to global disability, requires diverse therapeutic strategies. While psychological therapy and antidepressant medications are primary interventions, electroconvulsive therapy (ECT) emerges as a valuable option for severe and treatment ‑resistant cases. This retrospective observational study explores the scenery of depressive disorder‑related hospitalizations in Portuguese public hospitals from 2008 to 2015.